Social media and democracy : the state of the field, prospects for reform - Persily, Nathaniel; Tucker, Joshua A. (Joshua Aaron), 1971- (SSRC Anxieties of Democracy., 2020)
Over the last five years, widespread concern about the effects of social media on democracy has led to an explosion in research from different disciplines and corners of academia. This book is the first of its kind to take stock of this emerging multi-disciplinary field by synthesizing what we know, identifying what we do not know and obstacles to future research, and charting a course for the future inquiry. Chapters by leading scholars cover major topics - from disinformation to hate speech to political advertising - and situate recent developments in the context of key policy questions. In addition, the book canvasses existing reform proposals in order to address widely perceived threats that social media poses to democracy. This title is also available as Open Access on Cambridge Core.